Recommendation Versus Current Status: Retrospective Analysis of Age to Circumcise in a District Hospital - UPRAK, TEVFİK KIVILCIM (My University, 2023)
Introduction: Circumcision is one of the oldest and most frequently performed surgeries worldwide. The age of circumcision varies according to the country and region. We aimed to analyze the age of circumcision in our hospital. Methods: We evaluated the children who underwent circumcision at Istanbul Sultanbeyli State Hospital between February 2012 and February 2022. The following parameters were analyzed: age at operation, surgery date, and surgeon provider type. Children’s age at operation were categorized as follows: neonatal period (<30 days), infancy (≥31 days and <1 year), early childhood (≥1 year and <5 years), late childhood (≥5 years and <13 years), and adolescence (≥13 years and ≤17 years). Results: Seventeen thousand three hundred forty-five children were analyzed. Children’s ages ranged from 0 to 209 months; the median age was 4.07 [interquartile range (IQR) 1.82-6.33] years. The percentage of the neonatal period, infancy, early childhood, late childhood, and adolescence were 1.1%, 13.6%, 46.3%, 38%, and 1%, respectively. Urology performed the most circumcisions in any age group (8374, 48.3%), followed by general surgery (4818, 27.8%) and pediatric surgery (4153, 23.9%). In all surgeon provider types, circumcision was performed primarily in early childhood. Conclusion: Our study showed that most circumcision operations were performed in the inappropriate age range. A multidisciplinary effort is needed to implement healthcare professionals’ recommendations from the neonatal period. Keywords: Circumcision, male circumcision, age of circumcision, neonates, infant
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Circumcision; male circumcision; age of circumcision; neonates; infant